Effects of an Applied Load on the Chloride Penetration of Concrete with Recycled Aggregates and Recycled Powder - Zhiming Ma; Zhenhua Duan; Guangzhong Ba (Advances in Civil Engineering)
Recycled aggregate (RA) and recycled powder (RP) are the primary products of the reclamation of construction and demolition (C&D) wastes, and the question of how to use them to prepare recycled aggregate concrete (RAC) and recycled powder concrete (RPC) has been a hot topic in the construction industry in China. As concrete structures are frequently subjected to the effects of both applied loads and chloride attacks, it is necessary to examine their effects on both RAC and RPC, which have received little consideration in previous investigations. In this study, RAC and RPC were firstly prepared by using RA and RP, respectively, to replace natural coarse aggregate and cement by weight. For each type of recycled concrete, sustained load and repeated load tests were then conducted, followed by a chloride diffusion experiment after unloading. The results indicated that the chloride penetration increased with the loading degree as well as the repeated load cycles. As the RP used in this study has high fineness and activity, the chloride penetration of RPC was lower than that of natural concrete, while the opposite result was found in RAC. Besides, the correlation between the chloride diffusivity and the imposed loading damage was also established in this study.